Synthesis of Silicon‐Functionalized Dibenzosilaborins by Intramolecular BH/CH Dehydrogenative Cyclization and Their Tunable Photophysical and Chemical Properties by Silyl Groups. Issue 40 (11th September 2013) - Kawachi, Atsushi; Morisaki, Hiroshi; Hirofuji, Tatsuya; Yamamoto, Yohsuke
<x xml:space="preserve">Abstract</x> A bit borane: Silicon‐functionalized dibenzosilaborins were prepared by intramolecular BH/CH dehydrogenative cyclization of o‐(silyl)(hydroboryl)benzenes. The hydrosilyl derivative (X=H) can be converted into the fluorosilane (X=F) and chlorosilane (X=Cl). UV/Vis and fluorescence spectra are influenced by the functional groups X on the silicon atom through σ*–π* conjugation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>